Fine-root and leaf acquisitive traits decoupled from chloride accumulation in reflecting the differential salinity tolerance among Prunus hybrids - Zhou, Shuangxi; Walker, Rob R.; Edwards, Everard J. (Frontiers in Plant Science, 2025)
Improving crop salinity management requires enhanced understanding of salinity responses of leaf and fine-root traits governing resource acquisition, ideally in relation to ion accumulation at intra- or inter-specific levels. We hypothesized that these responses are coupled towards integrated resource conservation for plants under prolonged salt treatment. We tested the hypothesis with a glasshouse experiment on saplings of six contrasting Prunus hybrids, subjected to either control or salt treatment (reverse osmosis water versus 3.3 dS m-1 chloride solution containing mixed cations). Sample collections were carried out at 30 and at 60 days after the start of treatments. All six hybrids showed significantly higher lamina chloride concentration in response to salt treatment, with GF677 accumulating a lower concentration than the other five hybrids. There was significantly lower specific leaf area (SLA) in ‘Monegro’ and lower root tissue density (RTD) in ‘Nemaguard’ after 60 days – but not 30 days – of salt treatment. No hybrid showed concurrent significant decrease of SLA and specific root surface area (SRA) under salt treatment. The a priori known salinity-sensitive hybrid ‘Nemaguard’ not only showed decreased RTD and a negative relationship between root biomass and salt treatment duration, but also showed increased SRA without notable change of average root diameter. Lamina chloride accumulation and leaf gas exchange response were closely correlated along a gradient towards resource conservation from control to salt-treated plants in all hybrids, which was orthogonal to another gradient characterized by a hybrid-dependent modification of SLA, SRA, RTD and percentage of root length within the finest diameter class. This study highlighted the interspecific differential resource investment strategies, reflected by the hybrid-specific salinity-response coordination among leaf and fine-root acquisitive traits.